Harm Reduction Journal - Crofts, Nick; Lawson, Euan
Harm Reduction Journal publishes research focusing on the prevalent patterns of psychoactive drug use, the public policies meant to control them, and the search for effective methods of reducing the adverse medical, public health, and social consequences associated with both drugs and drug policies. We define 'harm reduction' as 'policies and programs which aim to reduce the health, social, and economic costs of legal and illegal psychoactive drug use without necessarily reducing drug consumption'.